On synergised and unsynergised pyrethrum. Their toxicity to Dysdercus cingulatus Fabricius and persistency of the toxic effect of the films. - Saxena, S. C.; Saxena, Y. (Contributions to Entomology = Beiträge zur Entomologie, 1965)
Dysdercus cingulatus Fabricius has been found very susceptible to pyrethrum and pyre-thrum -f- sulphoxide. Sulphoxide when mixed with the same concentrations of pyrethrum in the ratio of 1:1, act as synergist increasing the toxicity of the mixture and thereby giving a higher knockdown percentage of Dysdercus cingulatus. It is felt that this mixture may prove economical to control this pest, of cotton and other malvaceous plants.In viewr of the suggestion that sulphoxide increases the persistence of the toxicity of pyrethrum film, an experiment was specifically designed and it is suggested that irrespective of whether sulphoxide has any stabilizing effect on pyrethrum, since the pyrethrum becomes more toxic on adding sulphoxide, a longer persistent effect could be expected as the mixture of pyrethrum and sulphoxide being more toxic would take longer to loose its toxicity.